Menjadi Jawa : orang-orang Tionghoa dan kebudayaan Jawa di Surakarta, 1895-1998 - Rustopo, 1952-; Yayasan Nabil (Yogyakarta : Ombak bekerjasama dengan Yayasan Nabil, Jakarta, 2007)
History of Chinese assimilation process into Javanese culture in Surakarta and biographies of Chinese individuals active in Javanese performing arts and culture, 1895 to 1998
Revision of the author's thesis (doctoral)--Universitas Gadjah Mada, Yogyakarta, 2006
Includes bibliographical references (p. 345-371) and index
Keywords: Chinese -- Indonesia -- Surakarta -- History -- 20th century; Chinese -- Cultural assimilation -- Indonesia -- Surakarta -- History -- 20th century; Chinese -- Violence against -- Indonesia -- Surakarta -- History -- 20th century; Chinese -- Indonesia -- Surakarta -- Biography; Surakarta (Indonesia) -- Social conditions -- 20th century